EXAMINING THE ROLE OF THE SINGAPORE GOVERNMENT IN INCREASING ECONOMIC GROWTH IN THE DIGITAL ECONOMIC ERA - Ridwan; K.P.Suharyono S. Hadiningrat (Yayasan Inspirasi Merah Putih Indonesia, 2024)
Singapore's neo-classical economic model is a dynamic blend of state capitalism, urban planning, a thriving creative economy, well-crafted monetary policies, a robust welfare system, progressive education reforms, and effective fiscal strategies. Together, these components synergize to propel economic expansion, entice global talent, ensure political stability, and propel the digital revolution. This study delves into elucidating the pivotal role played by the Singaporean government in fostering digital economic evolution within the constructs of the neo-classical economic paradigm. Utilizing a qualitative research approach with a focus on literature review, the findings underscore the centrality of the state in driving digital economic transformation within the neo-classical economic framework. Acting as a primary catalyst, the government enhances economic growth through strategic interventions in education, healthcare, human capital development, housing, and financial progress, steering state-owned enterprises and international commerce towards advancement.